Draft Annual Plan 1978-79 Centrally Sponsored Schemes Union Territory of Pondicherry - Planning Commission (Planning Commission, 1978)
The Farmers Training Programme under the Centrally Sponsored Scheme commenced walking in their Union Territory from 1970 onwards. It caters to the needs of Pondicherry and Karaikal Regions at present.
Government of Pondicherry, Planning and Research Department